Using state-issued identification cards for obesity tracking. Issue 1 (January 2015) - Morris, Daniel S.; Schubert, Stacey S.; Ngo, Duyen L.; Rubado, Dan J.; Main, Eric; Douglas, Jae P.
Summary Obesity prevention has emerged as one of public health's top priorities. Public health agencies need reliable data on population health status to guide prevention efforts. Existing survey data sources provide county-level estimates; obtaining sub-county estimates from survey data can be prohibitively expensive. State-issued identification cards are an alternate data source for community-level obesity estimates. We computed body mass index for 3.2 million adult Oregonians who were issued a driver license or identification card between 2003 and 2010. Statewide estimates of obesity prevalence and average body mass index were compared to the Oregon Behavioral Risk Factor Surveillance System (BRFSS). After geocoding addresses we calculated average adult body mass index for every census tract and block group in the state. Sub-county estimates reveal striking patterns in the population's weight status. Annual obesity prevalence estimates from identification cards averaged 18% lower than the BRFSS for men and 31% lower for women. Body mass index estimates averaged 2% lower than the BRFSS for men and 5% lower for women. Identification card records are a promising data source to augment tracking of obesity. People do tend to misrepresent their weight, but the consistent bias does not obscure patterns and trends. Large numbers of records allow for stable estimates for small geographic areas.